A Sociolinguistic study on the interactions in selected Filipino blogs - Lopez, Garry C. (College of Arts and Letters, University of the Philippines Diliman, 2009)
This study looks at language as a tool for communication in Computer-Mediated Discourse. Being an emergent environment and medium, the Internet has influenced the way language of language users has been shaped. The aftermath is phenomenal and the distinct sociolinguistic characters drawn are highly interesting to explore. The blog articles used as data in this research are the recipients of Philippine Blog Awards 2008 single blog post division. This set of entries is used as representatives of the Philippine blogosphere. The analysis ha yielded communicative attributes, some of which resemble face-to-face interaction (e.g. interjections and fragmented utterances), while some of are exclusively used in a CMC environment (e.g. parenthetically enabled utterances, and hyperlinks). The study manifests Gumperz' idea that is the use of discourse strategies is a way to encourage co-interlocutors to engage in a conversational exchange.